Pengaruh Pendapatan Orang Tua Terhadap Tingkat Pendidikan Anak Petani - Aisyah Aisyah; La Ode Amaluddin; Fitriyani Saudi (Jurnal Penelitian Pendidikan Geografi, 2025)
The low level of education of children in Paruttellang Village is thought to be influenced by economic factors, especially the instability of parental income. The objectives of this study were to: 1) describe parental income; 2) describe the level of education of farmers' children in the village; and 3) determine the effect of parental income on the level of education of farmers' children in Paruttellang Village, Ngapa District, North Kolaka Regency. The method used was a quantitative method. This study was associative, namely research conducted to find the influence between one variable and another. The sample in this study were 45 parents of students in Paruttellang Village. Data were obtained through observation and questionnaire distribution. The analytical test tools used in testing this study were instrument tests, classical assumption tests, hypothesis tests, simple linear regression tests, and t-tests (partial). The results of the study showed that: 1) the majority of parents (56%) had incomes categorized as low; 2) the level of education of farmers' children was also still low, with 49% only attending elementary school; and 3) there was a significant influence between parental income on children's education levels, with a Sig. value. of 0.000 < 0.05 and the magnitude of the influence is 63.5%, while 36.5% is influenced by other factors that are not explained in this study.